2021
DOI: 10.3390/su132212585
|View full text |Cite
|
Sign up to set email alerts
|

Fostering a Clean and Sustainable Environment through Green Product Purchasing Behavior: Insights from Malaysian Consumers’ Perspective

Abstract: Rapid economic developments have led to the excessive consumption of environmental resources. Consumption patterns play a crucial role in deteriorating environmental conditions and influencing consumers to seek sustainability features while purchasing different products. The purpose of this paper was to analyze the sustainability factors that have prompted consumers in Malaysia to buy green products. The primary elements of this research focused on environmental concern, green product awareness, government sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 66 publications
(85 reference statements)
2
16
0
Order By: Relevance
“…The factors that were grouped in this category also refer to green product knowledge [ 40 , 50 , 63 , 65 ], natural environmental orientation [ 67 ], green habit [ 67 ], knowledge about environmental damage and pollution [ 71 ], attitudes toward environmental protection [ 71 ], environmental concern habit [ 40 ], environmental consciousness [ 37 , 58 , 61 , 64 ], attitudes toward environmental issues [ 64 ], green trust [ 40 , 50 , 54 , 66 ] green involvement [ 54 ], environmental beliefs [ 59 , 60 ], environmental awareness [ 5 , 50 , 59 ], environmental concerns [ 36 , 58 , 59 ], green attitudes [ 50 , 61 ], drive for environmental responsibility [ 36 , 42 ], perceived ecological value [ 44 ], green practices [ 46 ], green product awareness [ 44 , 45 ], and consumer social responsibility [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…The factors that were grouped in this category also refer to green product knowledge [ 40 , 50 , 63 , 65 ], natural environmental orientation [ 67 ], green habit [ 67 ], knowledge about environmental damage and pollution [ 71 ], attitudes toward environmental protection [ 71 ], environmental concern habit [ 40 ], environmental consciousness [ 37 , 58 , 61 , 64 ], attitudes toward environmental issues [ 64 ], green trust [ 40 , 50 , 54 , 66 ] green involvement [ 54 ], environmental beliefs [ 59 , 60 ], environmental awareness [ 5 , 50 , 59 ], environmental concerns [ 36 , 58 , 59 ], green attitudes [ 50 , 61 ], drive for environmental responsibility [ 36 , 42 ], perceived ecological value [ 44 ], green practices [ 46 ], green product awareness [ 44 , 45 ], and consumer social responsibility [ 54 ].…”
Section: Resultsmentioning
confidence: 99%
“…After excluding the work of Liu et al (2021) [ 34 ], the effect size of the public participation dimension was found to be 0.298. After excluding the work of Al-Kumaim et al (2021) [ 59 ], the effect size of the public participation dimension was found to be 0.311. However, after excluding the work of Chen et al (2020) [ 27 ], the effect size of the public participation dimension was found to be 0.476; for this reason, the work of Chen et al (2020) [ 29 ] was excluded as an anomalous study.…”
Section: Methods and Datamentioning
confidence: 97%
“…Research has shown that the importance of electric vehicles as a symbol of environmentalist self-identity is stronger among consumers who are concerned about climate change, thereby increasing the intention of these consumers to purchase electric vehicles [50]. GTTT products are typically novel green products that are designed to increase external environmental utility [51] more significantly than consumer utility. Therefore, environmentally conscious consumers tend to exhibit positive purchase intentions regarding GTTT products.…”
Section: Different Lifestyle Dimensionsmentioning
confidence: 99%
“…Such consumers also have a motivational need to enhance their personal status; thus, they also contribute to individuals' susceptibility to normative interpersonal influences, which leads to positive new product purchase intentions. GTTT products produce social utility via technological track changes and are typically novel green products on the market [51]. Thus, such products represent an orientation toward technological and product-related utility; and, as they are highly fashionable, novel, and environmentally efficacious, they can enhance the personal image and status of consumers.…”
Section: The Mediating Role Of Susceptibility To Interpersonal Influencementioning
confidence: 99%